Agricultural Management Options for Climate Variability and Change: AgroClimate - Clyde Fraisse (EDIS)
AgroClimate is a website providing climate information and decision-support tools to producers throughout the Southeastern United States. With information from the site, producers can develop a strategy for the coming season and track climate conditions that affect crop development and yield. This 4-page fact sheet was written by Clyde Fraisse and published by the UF Department of Agricultural and Biological Engineering, August 2012.